PTU-034 Stricture Formation after Endoscopic Mucosal Resection of Large Colonic Polyps. (17th August 2016) - Kassam, R; Subhani, J
Abstract : Introduction: Post endoscopic resection strictures are seen in oesophagus in up to 20–30% of circumferential resection. 1, 2 Probably due to the greater circumference of the colon these have not been described in Colorectal EMR. However with larger lesions being tackled the prospect of this complication arises. Methods: Details of lesions assessed for EMR by a single endoscopist (JMS) were kept prospectively. Non-pedunculated polyps >59 mm were assessed to see if the patients developed significant strictures. Only those who developed obstructive symptoms were considered significant. Results: here were 801 non Ip lesions, with 749 attempted resections on the database. There were 80 lesions >59 mm and 72 proceeded to attempted resection (8 not attempted all subsequently diagnosed as cancer). The 72 lesions will be the focus of the study. Mean size 68 mm (60–120 mm), 36 rectal, 15 other left-sided, 9 caecal, 12 other right-sided lesions. 23 (32%) involved 25–50% of the circumference, 35 (49%) 50–75% and 14 (19%) involved 75–100%. In 47/72 cases the resection was completed at the first session. In 25 cases the initial resection was stopped due to suspicion of CA, technical difficulty or length of procedure. 11/25 patients subsequently underwent surgery, 14 further endoscopic resection. After completed endoscopic resections 1 other patient required surgery. 60/72 treated endoscopically. 4 subsequently developed symptoms from strictures requiring dilation all had 75–100% circumferential involvement. 2 sigmoid (70, 100 mm), 2 rectal (90, 100 mm). All had LGD histology and only received a small amount of APC. 3 were completed in a single session, one required 2 sessions. Only 11 patients had >75% circumferential involvement and had complete endoscopic resection. 4 developed strictures. The 4 were treated with endoscopic dilation successfully. However, one patient who had twice been dilated to 15 mm, on a third session was dilated to 18 mm causing a perforation and subsequently required surgery. Conclusion: In large colorectal EMR if <75% of circumference involved there is little chance of functional significant structure. However if >75% there maybe a 40% chance of a functional significant stricture. Appropriate measures such as laxative and a 4 week endoscopic assessment is appropriate. References: 1 Bahin FF, et al. Endoscopy 2016 Jan;48 (1):71–4. 2 Komeda Y, et al. Endosc Int Open 2014 Jun;2 (2) E58–E64. Disclosure of Interest: None Declared